Rural to Urban Migration and Household Living Conditions in Bangladesh - Haque, M. Ershadul; Islam, M. Mazharul (Dhaka University Journal of Science, 2012)
This study examines the relationships between rural to urban migration status and household living conditions, using the 2007 Bangladesh Demographic and Health Survey (BDHS) data. The analysis finds significant living condition advantage of rural-urban migrants and urban natives over rural-natives, primarily linked to migration selectivity by education and occupation. Once the independent effects of education and occupation are controlled, association between migration status and living conditions remain significant but living condition advantage of rural-urban migrants and urban natives over rural natives fall down. The results imply that promoting higher education and opportunities for employment outside the agricultural or labour sectors (pull factor) are more likely to yield improved living conditions in Bangladesh. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11529 Dhaka Univ. J. Sci. 60(2): 253-257, 2012 (July)